2019
DOI: 10.1007/s10342-019-01241-y
|View full text |Cite
|
Sign up to set email alerts
|

Size-class structure of the forests of Finland during 1921–2013: a recovery from centuries of exploitation, guided by forest policies

Abstract: Frequency distributions of tree diameters are a powerful tool for analyzing changes of tree populations in large areas. We analyzed the densities and mean volume estimates of trees in different size classes for the Finnish forests over the time-span of the National Forest Inventories (1921-2013). The results display a general increase in trees in all size classes, species group and geographical area, mainly after the 1970s. The densities of medium-and large-sized conifers showed large increases in the southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A few previous studies have indicated that the general increase in forest cover and biomass in northern latitudes during recent decades ("greening effect") may be one factor behind increasing organic carbon concentrations in forested streams (Finstad et al, 2016;Nieminen et al, 2021;Škerlep et al, 2019), but ours is the first study showing that the trends in nitrogen concentrations may also correlate positively with the increase in forest biomass. Tree stand volume and latitude are positively correlated; tree stands with higher volume are found in southern rather than northern locations in the Nordic region (Henttonen et al, 2020), thus complicating the interpretation of the results. That is, it is unclear whether the increasing trends are primarily related to tree physicochemical processes, such as evapotranspiration and root exudates, or site locationrelated factors, such as temperature.…”
Section: Discussionmentioning
confidence: 99%
“…A few previous studies have indicated that the general increase in forest cover and biomass in northern latitudes during recent decades ("greening effect") may be one factor behind increasing organic carbon concentrations in forested streams (Finstad et al, 2016;Nieminen et al, 2021;Škerlep et al, 2019), but ours is the first study showing that the trends in nitrogen concentrations may also correlate positively with the increase in forest biomass. Tree stand volume and latitude are positively correlated; tree stands with higher volume are found in southern rather than northern locations in the Nordic region (Henttonen et al, 2020), thus complicating the interpretation of the results. That is, it is unclear whether the increasing trends are primarily related to tree physicochemical processes, such as evapotranspiration and root exudates, or site locationrelated factors, such as temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Norway spruce larger than 50 cm are rarely found in boreal old-growth forests in the Nordic countries (Linder 1998;Siitonen et al 2000;Kuuluvainen et al 2002;Rouvinen and Kuuluvainen 2005). This study's dataset can therefore be regarded as covering the whole age and diameter range from young to oldgrowth stands (Henttonen et al 2020), but not necessarily as a representative sample, because the locations of the experiments and plots were subjectively selected. We found that tree survival did not differ between the used datasets (HARKAS, the Norwegian dataset, and old-growth stands).…”
Section: Discussionmentioning
confidence: 99%
“…The study area was divided into three south, middle, and north zones which roughly followed the hemi-boreal/south boreal, mid-boreal, and north boreal/forest tundra vegetation zones. Separate models were computed for these zones (Figure 1) [45,46].…”
Section: Models For Variable Estimation 241 Land Cover Classificationmentioning
confidence: 99%